Implikasi Penurunan Tarif PPH Badan Berdasarkan Perppu 1 Tahun 2020 Terhadap Akuntansi Pajak Penghasilan - Suharno Suharno (LPPM-STPI, 2020)
The income tax rate adjustment in Government Regulation In Lieu of Law (Perppu) 1/2020 has significant implications for the accounting treatment of income tax as described in Paragraph 47 of PSAK 46. As the consequences, a company (a taxpayer) has to adjust its income tax accounting records. The tax accounting treatment affected by the rate reduction policy is (i) current tax, (ii) deferred tax assets/liabilities (iii) income tax payable under Article 25 and (iv) tax calculation at the end of the year.